Bubbles and Monetary Policy: To Burst or not to Burst? - Philipp König; David Pothier (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The question of whether monetary policy should target asset prices remains a contentious issue. Prior to the 2007/08 financial crisis, central banks opted for a wait-and-see approach, remaining passive during the build-up of asset price bubbles but actively seeking to stabilize prices and output after they burst. The macroeconomic and financial turbulence that followed the subprime housing bubble has led to a renewed debate concerning monetary policy's role in maintaining financial stability. This Round-Up provides a brief overview of this topic.
Keywords: 330